Pre-pregnancy Maternal Weight and Gestational Weight Gain Increase the Risk for Childhood Asthma and Wheeze: An Updated Meta-Analysis - Liu, Shufang; Zhou, Bo; Wang, Yunfeng; Wang, Kundi; Zhang, Zhixin; Niu, Wenquan (Frontiers in Pediatrics, 2020)
Background: Mounting evidence suggests that childhood asthma is closely associated with maternal weight before pregnancy and gestational weight gain (GWG), yet the results are not often reproducible. Objectives: We conducted a comprehensive meta-analysis, aiming to evaluate the association of pre-pregnancy maternal obesity or overweight and high GWG with the risk for childhood asthma and wheeze. Methods: Literature search, quality assessment, and data extraction were completed independently and in duplicate. Effect-size estimates are expressed as odds ratio (OR) with 95% confidence interval (CI). Results: Twenty-two observational studies involving 145,574 mother-child pairs were meta-analyzed. In overall analyses, maternal obesity or overweight in pre-pregnancy significantly increased the risk of both childhood asthma and wheeze (adjusted OR: 1.41 and 1.13, 95% CI: 1.26-1.59 and 1.07-1.20, both p <0.001). Per 1 kg/m2 increment in maternal body mass index was associated with a significantly increased risk of childhood asthma and wheeze (adjusted OR: 1.03, 95% CI: 1.02-1.03, p <0.001). Compared with normal GWG, very high GWG (adjusted OR: 1.24, 95% CI: 1.04-1.47, p: 0.018), moderate high GWG (adjusted OR: 1.12, 95% CI: 1.04-1.21, p: 0.004), and very low GWG (adjusted OR: 1.26, 95% CI: 1.08-1.47, p: 0.004) increased the risk of childhood asthma and wheeze. There was a low probability of publication bias. Conclusions: Our findings indicate that both pre-pregnancy maternal obesity or overweight and very to moderate high or low GWG render their offspring susceptible to a significantly increased risk of having childhood asthma and wheeze.